Changing change management: the intranet as catalyst - Pitt, Leyland; Murgolo-poore, Marie; Dix, Steve (Henry Stewart Publications, 2001)
The nature of corporate change is different now from what it was a decade or more ago. Whereas organisational change was typically an initiative or project, today it tends to be an ongoing process, as organisations strive to keep abreast of turbulent environments. The corporate intranet has emerged not only as a medium through which to communicate the information needed for the members of organisations to collaborate, but as an instrument for change itself. This paper considers the corporate intranet as catalyst, and briefly reviews the successes of global firms where corporate intranets have both caused and facilitated change. It then introduces I-CAT, a pencil and paper checklist for the assessment of the intranet's effectiveness as a catalyst. Results of a benchmark study are presented, as well as those of I-CAT surveys in a range of organisations, some successful and some less so. The paper concludes by suggesting implications for managers, as well as identifying avenues for further investigation by researchers and consultants.